Peran Pemerintah Daerah Dalam Pelaksanaan Ibadah Haji Di Sulawesi Utara - Fitrianti S. Panambang; Nurfazria Baid; Nadia Paputungan; Abdul Latif (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This paper explores the role of local government in managing the implementation of the Hajj pilgrimage in North Sulawesi. Its background reflects a significant increase in the number of Hajj pilgrims from the region and the challenges faced by the local government in organizing the pilgrimage process. The research focuses on policy analysis and efforts undertaken by the government to provide facilities, manage transportation, accommodation, and other related services. The primary conclusion underscores the crucial and active role of the local government in ensuring the smoothness and safety of Hajj pilgrims while fulfilling their needs throughout the journey. The novelty of this work lies in its in-depth analysis of the specific role of the local government in the context of the Hajj pilgrimage in North Sulawesi, serving as a guideline for other regions facing similar challenges in managing the pilgrimage for their pilgrims.